2018
DOI: 10.1021/acssensors.8b00158
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Analyte Fluorescent Sensor Based on [5]Helicene Derivative with Super Large Stokes Shift for the Selective Determinations of Cu2+ or Zn2+ in Buffer Solutions and Its Application in a Living Cell

Abstract: A new fluorescent sensor, M201-DPA, based on [5]helicene derivative was utilized as dual-analyte sensor for determination of Cu or Zn in different media and different emission wavelengths. The sensor could provide selective and bifunctional determination of Cu in HEPES buffer containing Triton-X100 and Zn in Tris buffer/methanol without interference from each other and other ions. In HEPES buffer, M201-DPA demonstrated the selective ON-OFF fluorescence quenching at 524 nm toward Cu. On the other hand, in Tris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 57 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…As expected, the characteristic emission intensity of 1 at 614 nm in the presence of cys is enhanced about thrice as intense as the emission band of the 1 ‐based Cu‐quenching system in the absence of cys, indicating that the “off‐on” FL sensor based on detecting Cu 2+ ion is effectively recovered with the addition of cys (Figure a). Identically, with the addition of the polar and positively charged amino acid such as lys, the polar and negative charged amino acid such as glu, polar neutral amino acids such as gly and thr, the emission intensity of the 1 ‐based Cu 2+ ‐quenching system could be hardly enhanced due to the lack of chelation interaction with the Cu 2+ ion (Figure b) ,. [10a], The above results fully prove that the 1 ‐based Cu 2+ ‐quenching system is selective to detect cys.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…As expected, the characteristic emission intensity of 1 at 614 nm in the presence of cys is enhanced about thrice as intense as the emission band of the 1 ‐based Cu‐quenching system in the absence of cys, indicating that the “off‐on” FL sensor based on detecting Cu 2+ ion is effectively recovered with the addition of cys (Figure a). Identically, with the addition of the polar and positively charged amino acid such as lys, the polar and negative charged amino acid such as glu, polar neutral amino acids such as gly and thr, the emission intensity of the 1 ‐based Cu 2+ ‐quenching system could be hardly enhanced due to the lack of chelation interaction with the Cu 2+ ion (Figure b) ,. [10a], The above results fully prove that the 1 ‐based Cu 2+ ‐quenching system is selective to detect cys.…”
Section: Resultssupporting
confidence: 53%
“…The FL quenching can occur through diverse pathways such as energy transfer, molecular rearrangement, electrostatic interaction, and dynamic collision, etc , . It is found that the FL behavior of the 1 ‐based sensor exhibits a rapid “on‐off” switch when the Cu 2+ ion is introduced to the sensing system, the possible quenching mechanism of the Cu 2+ ion for the 1 ‐based sensor maybe that the LMCT absorption of the Cu 2+ ion hinders energy transfer from ST fragments to the Eu 3+ ion in the skeleton of 1 in aqueous solution . To further explore the detecting mechanism of the 1 ‐based sensor towards the Cu 2+ ion, the ESI‐MS test of 1 in aqueous solution in the presence of the Cu 2+ ion has been carried out and exhibits that the m/z peaks remain unchanged after adding the Cu 2+ ion, demonstrating that the Cu 2+ ion has no obvious bonding interactions with the polyoxoanion of 1 (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other common methods for Hg 2+ detection, fluorescent chemosensors have received considerable attention because of their distinct advantages (Nolna and Lippard, 2008;Zhang et al, 2008;Lee et al, 2015;Xie et al, 2015;He et al, 2016;Sakunkaewkasem et al, 2018;Bai et al, 2019;Yuan et al, 2019). As a result, a growing number of fluorescent chemosensors for Hg 2+ have been reported in the past few decades (Chen et al, 2011;Wang et al, 2012;Park et al, 2013;Cheng et al, 2015;Hong et al, 2016;Lee et al, 2016;Erdemir et al, 2017;Bai et al, 2018;Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The major deficiencies of Zn 2+ probes reported are the interference from other transition metal ions, especially Cd 2+ , due to in the same group of the Periodic table and similar properties. [20][21][22] Although a small amount of fluorescent probe is enhanced, its fluorescence excitation and emission wavelengths (usually less than 350 and 500 nm) are shorter, which suffers from background interference and low collection efficiency in deep-tissue imaging. [23] Therefore, the development of a Zn 2+ probe with high sensitivity and selectivity has shown tremendous potential in the biomedical applications.…”
Section: Introductionmentioning
confidence: 99%